Maximal Aerobic Power Using the Modified Heck Protocol: Prediction Models - Parpa, Koulla; Michaelides, Marcos A. (International Journal of Sports Medicine, 2022)
The purpose of this study was to develop prediction models based on an incremental treadmill test to volitional exhaustion utilizing the modified Heck protocol. A total of 598 professional and youth athletes participating in different sports were recruited for this study. Specifically, the study enrolled professional male soccer players (n=380), professional male futsal players (n=24), elite male basketball players (n=27), professional male soccer referees (n=50), elite female soccer players (n=19), youth male basketball players (13–14 yrs n=15, 15–17 yrs n=20) and youth male soccer players (15 yrs n=28, 16–17 yrs n=35). Anthropometric measurements included stature, body mass, and body fat. Furthermore, all participants performed incremental cardiopulmonary exercise testing on a treadmill using the modified Heck protocol. Through multiple regression analysis, a separate prediction model was developed for each of the athletic populations. Results demonstrated that a significant (p=0.001) proportion of the variation observed in VO2max was explained by the variation in running time. The generated VO2max regression equations would allow athletes and coaches to predict VO2max in a relatively short time without the need for expensive and sophisticated equipment. To our knowledge, this is the first study that provides regression models for different athletic populations using the modified Heck protocol.
Keywords: VO2max; soccer; futsal; basketball